Didactical Reduction of Teaching Materials of Spermatophytes To Make Easier on Information Processing and To Reduce Mental Effort of Senior High School Student - Santi Sri Rahayu Prajayanti; Topik Hidayat; Adi Rahmat (Universitas Sebelas Maret, 2015)
This research aims to facilitate students in processing teaching material information and reducing student mental effort in Spermatophytes learning. This study using posttest only control group design. The subject for this study is the tenth class of MIA at one of Ciamis Senior High School which consist of 34 control-class students and 37 experiment-class students. Teaching in control-class use regular biology textbook from their school, then for teaching in experiment-class use flowchart as result of didactical reduction process. Information processing of the student is measured by task complexity worksheet and student mental effort is measured by questionnaire subjective rating scale (Likert scale). Student learning outcomes are measured on aspects of reasoning using pencil test. The data were analyzed statistically with mean test and correlation test. Research outcome showing that studentsinformation processing at experiment-class is higher and have significant difference than control-class. The high value of information processing and low value mental effort students in the experimental-class was significantly correlated with higher learning outcomes. This outcome show that didactical reduction can facilitate students for processing teaching material and reduce students mental effort so the teaching outcomes become better.Keywords: Didactical reduction, spermatophytes teaching material